Applications and Analysis of Artificial Intelligence in Modern Education - Guo, Jinrong (Transactions on Computer Science and Intelligent Systems Research, 2025)
The application of artificial intelligence in education has changed the traditional teaching methods and provides innovative solutions to enhance learning experiences and effects. This study analyzes the significance of artificial intelligence in modern education and its impact on educational methods. The study also examines artificial intelligence applications in contemporary education, including machine learning, deep learning, and natural language processing. Specifically, this paper examines artificial intelligence in personalized learning, intelligent assessment systems, and interactive educational platforms. The study is conducted using a comprehensive dataset derived from multiple educational institutions, and the results demonstrate that artificial intelligence significantly improves student engagement and academic performance. Experimental outcomes show that artificial intelligence-driven educational tools adapt effectively to individual learning needs, providing tailored support and resources. The practical implications of this research highlight artificial intelligence’s potential to transform education by creating more inclusive and efficient learning environments. These findings underscore the importance of integrating AI technologies into modern educational frameworks to foster personalized and scalable learning solutions.